Deciphering the mechanism of action of VP343, an antileishmanial drug candidate, in Leishmania infantum - Sameh Obeid; Eloisa Berbel-Manaia; Valérie Nicolas; Indira Dennemont; Julien Barbier; Jean-Christophe Cintrat; Daniel Gillet; Philippe M. Loiseau; Sébastien Pomel (iScience, 2023)
Summary: Antileishmanial chemotherapy is currently limited due to severe toxic side effects and drug resistance. Hence, new antileishmanial compounds based on alternative approaches, mainly to avoid the emergence of drug resistance, are needed. The present work aims to decipher the mechanism of action of an antileishmanial drug candidate, named VP343, inhibiting intracellular Leishmania infantum survival via the host cell. Cell imaging showed that VP343 interferes with the fusion of parasitophorous vacuoles and host cell late endosomes and lysosomes, leading to lysosomal cholesterol accumulation and ROS overproduction within host cells. Proteomic analyses showed that VP343 perturbs host cell vesicular trafficking as well as cholesterol synthesis/transport pathways. Furthermore, a knockdown of two selected targets involved in vesicle-mediated transport, Pik3c3 and Sirt2, resulted in similar antileishmanial activity to VP343 treatment. This work revealed potential host cell pathways and targets altered by VP343 that would be of interest for further development of host-directed antileishmanial drugs.